Psychosocial impact of cancer cachexia. Issue 2 (16th April 2014) - Hopkinson, Jane B.
Abstract : Background: Cancer cachexia has impact on patients and their family members. Patients experience loss of weight often accompanied by anorexia and other debilitating symptoms that have clinical impact and impact everyday life. The importance of understanding this impact lies in (1) the alleviation of cachexia‐related suffering and (2) its implications for treating cachexia. Review: Two decades of exploratory investigation of the manifestations, meaning and management of cancer cachexia reveal emotional and social impacts for both patients and their carers. Patients can describe change in appearance and loss of physical strength often accompanied by change in eating habits (amount, type and pattern of food intake). The psychosocial effects can include loss of independence, sense of failure, sense of helplessness, conflict with family members over food, social isolation and thoughts of death. They are effects that can distress. Conversely, weight loss, especially early in its course and for those who are obese, can be perceived as beneficial, which inhibits self‐management of diet and physical activity. Conclusion: Models of the psychosocial effects of cancer cachexia have been developed, leading to, as yet unproven, propositions of how negative patient and family impacts can be addressed. This literature overlooks the potential importance of psychosocial intervention to emerging multimodal treatments for the multicausal syndrome. Psychosocial intervention in cachexia should be tested for potential to help people affected by cancer cachexia feel better but also for potential to make people better by aiding uptake and compliance with multimodal therapy.